Diabetes mediates an inverted L-shaped association between cardiometabolic index and kidney stones: a cross-sectional study from NHANES 2007-2020 - Bi, Jinghui; Du, Jianwei; Yan, Xiaoyi; Chen, Rongxin (Frontiers in Endocrinology, 2025)
BackgroundKidney stones are a chronic metabolic disorder. The cardiometabolic index (CMI) is a new and easily accessible measure used to assess metabolic status. However, the relationship between CMI and the incidence of kidney stones remains unclear.MethodsData from the National Health and Nutrition Examination Survey (NHANES) was used in our cross-sectional study. A weighted multivariable logistic regression analysis was conducted to assess the relationship between CMI and kidney stone incidence. Subgroup and restricted cubic spline regression analyses were utilized to confirm robustness and assess the non-linearity of the association between CMI and kidney stone incidence.ResultsThis study involved 18,043 individuals, of whom 9.89% were diagnosed with kidney stones. After controlling for all covariates, CMI showed a significant positive association with kidney stone incidence (OR: 1.07, 95%CI: 1.02-1.12). Individuals in the highest CMI quartile experienced a 50% higher incidence of kidney stones than those in the lowest quartile (OR: 1.50, 95%CI: 1.18-1.92). Additionally, a significant interaction was observed in the subgroup with a history of diabetes (p < 0.05).ConclusionThe study identified a notable non-linear relationship between elevated CMI levels and a greater occurrence of kidney stones. This finding suggests that by routinely monitoring CMI levels, physicians can identify individuals at risk for kidney stones early, allowing for timely intervention to mitigate disease progression.